Remediation of Pasture Dieback Using Plant Growth Promotant - Maria M. Whitton; Xipeng Ren; Sung J. Yu; Tieneke Trotter; Dragana Stanley; Yadav S. Bajagai (Agronomy, 2022)
Pasture dieback is a syndrome of unknown cause affecting grasses in Australia, creating significant economic losses to farmers by reducing available livestock feed and paddock carrying capacity. RC3 is a commercial plant growth stimulant tri-sodium salt of trimercapto-S-triazine (TMT) and potassium humate as active ingredients. TMT is commonly used for soil and wastewater remediation by capturing and binding heavy metals, while potassium humate is an organic compound used as a plant growth promoter. We investigated the ability of RC3 to restore soil health and productivity under pasture dieback conditions. RC3 was applied on pasture dieback affected paddock replicate plots once, at a rate of 4 mL/m2, and soil core samples were taken weekly to analyse microbial communities. Plants were collected regularly to measure dry matter and plant morphometrics. Twenty weeks after a single application, dry matter increased in RC3 plots by 900 kg/ha compared to control plots, and at week 48, eleven months after the single application, RC3 plots showed a trend of more grass and dicot species than the control. Morphometric measures suggest minor improvements in dicotyledon plants. Alpha diversity did not change with the application of RC3. Temporal correlation analysis shows that RC3 steadily reduced the presence of genera predominant in poor soils and with extreme environmental conditions over time and prevented the decline of beneficial genera, such as Marmoricola, Actinomadura, Dactylosporangium, and mle1-7.